The UK Government’s Troubled Families Programme: Delivering Social Justice? - Crossley, Stephen ca. 20./21. Jh. (Social Inclusion, 2018)
This article examines and reviews the evidence surrounding the UK Government’s Troubled Families Programme (TFP), a flagship social policy launched in 2011, following riots in towns and cities across England. The programme aims to work with over 500,000 ‘troubled families’ by 2020, using a ‘whole family’ intervention. It has been beset by controversy and criticism since its inception, but it has been described by the government as ‘promoting social justice’. Drawing on Nancy Fraser’s work around recognition and redistribution, this article assesses the subjective aims and achievements of the TFP and locates this analysis in the wider objective conditions experienced by disadvantaged families in the UK at the current time.